PEMESANAN PERSEDIAAN BAHAN BAKU NATA DE COCO DI PD. SUCI SEGAR - , Yogaswara; Yusuf Mauluddin (Institut Teknologi Garut, 2016)
This research study about planning of water supply of coconut for the raw material of making of nata de coco in PD.Suci Segar. Problems that happened is often the happening of the raw material insuffiency effect of not yet the existence of supply planning. To solve problem the used by method EOQ is that got by a policy sum up the water supply of coconut which must in message ( Q ), reorder point ( Rop ),lead time ( L ), and safety stock ( ss ). Pursuant to result analyse with the the policy so that insuffiency of water supply of coconut is not happened and also fare of insuffiency of total persedian dang fare of low supply.